2021
DOI: 10.1590/1413-785220212905244505
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the Walant Technique Against the Covid-19 Pandemic

Abstract: Objective: Evaluate the experience of private and public health services with the WALANT procedure in the COVID-19 pandemic. Methods: This is a retrospective, multicenter longitudinal study gathering cases of hand surgery subjected to the WALANT technique in the Hospitals Dr. Radamés Nardini and IFOR during the COVID-19 pandemic (August 2020). As a parameter, the verbal numerical rating scale for twenty patients referring to the preoperative, intraoperative and postoperative periods was applied. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…High patient satisfaction rates have been reported both in the United States and abroad. 2,3,6,7,10,12,14,25,[43][44][45][46] Our study found similar results, with 99% of patients rating their experience as better than or the same as going to the dentist. Ninety-nine percent of our patients would recommend wide-awake hand surgery to a friend or family member and would also do surgery while wide awake again if needed.…”
Section: Discussionsupporting
confidence: 75%
“…High patient satisfaction rates have been reported both in the United States and abroad. 2,3,6,7,10,12,14,25,[43][44][45][46] Our study found similar results, with 99% of patients rating their experience as better than or the same as going to the dentist. Ninety-nine percent of our patients would recommend wide-awake hand surgery to a friend or family member and would also do surgery while wide awake again if needed.…”
Section: Discussionsupporting
confidence: 75%
“…Comparative reports presented in literature between Wideawake local anesthesia no tourniquet versus local anesthesia for minor hand operations (Carpal tunnel syndrome, Trigger finger, De Quervain's) support that WALANT is an alternative anesthetic technique that, provides better comfort for the patient, decreased pain during surgical procedure, creates bloodless surgical field, provides patient safety and efficacious anesthesia [14,15] . WALANT procedure was not initially accepted by hand surgeons until the pandemic period of COVID-19, with the lack of anesthesiologists to cover other areas of health, brought back to the fore and the good outcomes from its application began to be published slowly [12,25,26] . Sutcliffe et al(2022) reported that in pandemic Covid -19 period British Society for Hand Surgery encourage and suggest the use of WALANT technique and propose that the use of respective procedure of anesthesia for hand surgery injury should continue and increase beyond the current pandemic based the advantages which offers.12 Rutereana et al(2022) reported that during Covid-19 period WALANT was a safe and effective anesthetic method in hand surgery and must be included in surgical training with scope to optimize day to day operative care and confrontation future crises, while Alves et al(2012) suggested that with WALANT technique the post-surgical hospitalization time is shorter generating greater benefits to patients̓ health and in future hand surgery service must be able to perform this anesthetic procedure, in their daily surgery routine, due to its benefits [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard we can inject analgesia if the patient complains of any pain during the surgery. During the COVID-19 pandemic, the WALANT technique gained popularity since it did not require intubation and the patients were quickly discharged after surgery [ 7 ].…”
Section: Clinical Discussionmentioning
confidence: 99%